Design and Validation of Stress Management Training Program for First-Grade Female High School Teachers in Shahriar City - Nikookar, Zahra; Ahghar, Qodsi; Ahmadi, Amineh (Iranian Journal of Educational Sociology, 2022)
Introduction: The purpose of this study was to design a stress management training program and determine its effectiveness on the quality of work life, career engagement and professional ethics for high school teachers. Methodology: The research was done in a mixed method in two stages. The first stage was qualitative that training package was created and the second stage was quantitative, implemented in the form of factor analysis. The statistical population in the qualitative section included scholars and academic experts (psychologists and educational management) as well as those who had specialized research studies in this field. Purposeful sampling method was used to determine the samples. The sample size in this section was 12 ones based on the saturation principal. The statistical population of the quantitative section included all first-grade female high school teachers in Shahriar City in 2018. 474 ones were randomly selected and filled out the questionnaires. After designing the program, it was validated based on theoretical foundations and semi-structured interviews with teachers and experts in the field of psychology. According to the literature review, seven factors were identified using the exploratory factor analysis. Findings: Based on the study on this field, the first factor was the recognition of tensions, the second one was expression, the third one was the anger management skill, the fourth one was replacing rational thoughts, the fifth one was the rational behavior skill, the sixth one was the time management, and the seventh one was called self-relaxation. Conclusion: Stress management techniques are used successfully in many emotional and physical problems such as anxiety, depression, insomnia, and career problems, and are effective.